Kapitał naturalny miast w łagodzeniu skutków antropogenicznej zmiany klimatu - Krauze, Kinga (Public participation in urban climate policy making: The example of Lodz, 2024)
Natural capital plays a key role in mitigating the effects of climate change in cities. It includes all resources of nature, ecosystems as such and the ecological processes that occur within them. We use a percentage of nature’s potential in the form of goods (food, fossil resources, water) as well as services, e.g. soil formation, pollination, climate regulation. The share of goods and services used by humans is called ecosystem services. In a city, natural capital is formed by fields, meadows and forests as well as parks, squares and common lawns, in addition to water bodies. Green spaces help to absorb carbon dioxide, improve air quality and reduce the urban heat island effect. They thus improve the living conditions of residents while reducing the risks associated with phenomena such as droughts, heat and flooding. The risks arise not only directly from weather conditions, but also from a number of adverse feedbacks. Prolonged droughts, for example, result in increase in airborne allergens. Green areas through increasing air humidity, prevent dust formation and bind particles due to the increased roughness of the substrate and the structure of leaves and greenery (density, size, stratification, individual characteristics of species). Green areas also influence the water cycle. Plants use water, capture rainfall it in their crowns, their roots improve infiltration, mulch increases the water holding capacity of the soil. Ecosystem services depend on the health of nature as measured, among other things, by biodiversity. Strengthening public awareness of the importance of natural capital and the impact of human activities on the environment is therefore a prerequisite for sustainable urban development.